Cholesteatoma disease recidivism after canal wall up tympanomastoidectomy with or without obliteration (CLEAR-EAR): A protocol for a randomized controlled trial - Chiara Erfurt; Maud J. de Rooij; Robert J. Stokroos; Louise V. Straatman; Hans G. X. M. Thomeer (PLoS ONE, 2026)
Background and rationale Cholesteatoma treatment relies on surgery with disease removal as the primary goal. While canal wall down (CWD) and canal wall up (CWU) tympanomastoidectomy remain standard approaches, mastoid obliteration has gained popularity. Canal wall up preserves ear canal anatomy and adding the obliteration technique suggests lower recurrence and residual rates. However, controversy persists and surgical consensus is lacking. Current decision-making relies on personal experience and patient-related factors rather than high-quality evidence. This study therefore investigates whether CWU with obliteration reduces cholesteatoma recurrence and residual disease compared to CWU without obliteration, by comparing recidivism rates for both interventions. Additionally, complications, hearing outcomes, quality of life and economic evaluation will be assessed. This study will assess long-term outcomes with a follow up of 5 years. Methods This multicentre single-blind randomized controlled trial (RCT) will include 178 adults undergoing CWU tympanomastoidectomy for cholesteatoma removal, randomized in a 1:1 ratio to CWU with obliteration or without obliteration. Recurrent or residual disease is assessed by micro-otoscopy at 6–18 weeks and by micro-otoscopy and DW-MRI at one, three, and five years postoperatively. Suspected disease is confirmed during revision surgery when indicated. Secondary outcomes include hearing, complications, quality of life, and economic evaluation. Discussion This is the first prospective RCT comparing CWU with and without obliteration. By establishing the follow-up period at five years, we aim to assess the true rates of recidivism, as literature indicates that most recurrent diseases are detected several years after surgery, with incidence appearing to rise approximately three years postoperatively. Key strengths include comparative hearing outcome assessment, quality of life evaluation, and economic evaluation. This multicentre trial aims to provide high-quality evidence to inform clinical guidelines and support evidence-based decision-making in cholesteatoma treatment. Trial registration Netherlands Trial Register (CCMO): NL86362.041.24. Registered on 13 March 2025.